The global burden of HIV-associated cryptococcal infection in adults in 2020: a modelling analysis. Issue 12 (December 2022) - Rajasingham, Radha; Govender, Nelesh P; Jordan, Alexander; Loyse, Angela; Shroufi, Amir; Denning, David W; Meya, David B; Chiller, Tom M; Boulware, David R
Summary: Background: Cryptococcal meningitis is the most common cause of meningitis in adults living with HIV in sub-Saharan Africa. The estimates of national, regional, and global burden of cryptococcal meningitis are essential to guide prevention strategies and determine needs for diagnostic tests and treatments. We present a 2020 estimate of the global burden of HIV-associated cryptococcal infection (antigenaemia), cryptococcal meningitis, and cryptococcal-associated deaths. Methods: We defined advanced HIV disease as adults with a CD4 count of less than 200 cells/μL, as this group is at highest risk for cryptococcosis. We used UNAIDS estimates (2019–20) and population-based HIV impact assessment surveys (2016–18) to estimate the number of adults with CD4 counts of less than 200 cells/μL at risk for cryptococcosis, by country and region. Secondly, we summarised cryptococcal antigenaemia prevalence in those with a CD4 count of less than 200 cells/μL by reviewing published literature. Thereafter, we calculated the number of cryptococcal antigen (CrAg)-positive people in each country and region by multiplying the number with advanced HIV disease at risk for cryptococcal infection by the cryptococcal antigenaemia prevalence of the respective country or region. We estimated progression from cryptococcal antigenaemia to meningitis or death based on estimates from the published literature. Findings: We estimated that there were 4·3 million (IQR 3·0–4·8) adults with HIV and CD4 counts of less than 200 cells/μL globally in 2020. We calculated a mean global cryptococcal antigenaemia prevalence of 4·4% (95% CI 1·6–7·4) among HIV-positive people with CD4 counts of less than 200 cells/μL, corresponding to 179 000 cases (IQR 133 000–219 000) of cryptococcal antigenaemia globally in 2020. Annually, we estimated that there are 152 000 cases (111 000–185 000) of cryptococcal meningitis, resulting in 112 000 cryptococcal-related deaths (79 000–134 000). Globally, cryptococcal disease accounts for 19% (13–24) of AIDS-related mortality. Interpretation: Despite a reduction in the estimated absolute global burden of HIV-associated cryptococcal meningitis compared with 2014, likely to be due to antiretroviral therapy expansion, cryptococcal disease still accounts for 19% of AIDS-related deaths, similar to 2014 estimates. To end cryptococcal meningitis deaths by 2030, cryptococcal diagnostics, meningitis treatments, and implementation of preventive screening are urgently needed. Funding: None.